Working against Labor: Struggles for Self in the Indian Construction Industry. (5th November 2020) - Sargent, Adam
Abstract: From the outside, India's urban construction sites appear to be places of toil, yet for workers, the material qualities of particular actions, from carrying bricks to cutting marble, are experienced as either self‐affirming work or abject labor. This article explores how construction workers understand and intervene in the meaning of their work. Skilled and semi‐skilled workers are particularly attentive to the bodily shifts brought on by work, as well as the varied recognition of such shifts by others. The formulation of a superior's command, along with callouses, capacities, and the aches induced by work are all understood as elements of an unstable process of transformation. Workers are constantly on guard to ensure that their work, envisioned as a specific bodily capacity, does not devolve into labor or undifferentiated toil. By refusing to perform tasks that they consider labor, these workers simultaneously assert control over the conditions of their productive activity and recreate an embodied form of class distinction. I argue that such refusals and contestations constitute a politics of work that poses particular limitations but also possibilities for envisioning the nature of capitalist work more generally.